2019
DOI: 10.1002/fee.2141
|View full text |Cite
|
Sign up to set email alerts
|

Successful molecular detection studies require clear communication among diverse research partners

Abstract: Molecular detection techniques are powerful tools used in ecological applications ranging from diet analyses to pathogen surveillance. Research partnerships that use these tools often involve collaboration among professionals with expertise in field biology, laboratory techniques, quantitative modeling, wildlife disease, and natural resource management. However, in many cases, each of these collaborators lacks specific knowledge about the approaches, decisions, methods, and terminology used by their research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In addition, the lack of clear communication of novel genetic methods and results (including transparency and reproducibility) to relevant stakeholders can be prohibitive in translating these findings to appropriate management and eradication action on the ground (Mosher et al , Ward et al ). These communication challenges have been well documented in relation to the marine sector (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the lack of clear communication of novel genetic methods and results (including transparency and reproducibility) to relevant stakeholders can be prohibitive in translating these findings to appropriate management and eradication action on the ground (Mosher et al , Ward et al ). These communication challenges have been well documented in relation to the marine sector (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As with any study, defining the question to be addressed is the first step and the design of the eDNA assay depends upon the scope of the study 26 . For instance, if the goal of the research or survey is to detect one or a few species, a targeted probe-based assay is best.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the design of multiple assays for testing may be limited by sequence availability, and compromise may be necessary on aspects of assay performance. These choices must be guided by the goals of the study and must be reported with the results 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of using (e)DNA metabarcoding in NIS surveillance can be obvious for researchers dealing with it, but may seem much more complex and difficult for environmental managers and stakeholders who are new or untrained in DNA-based methods. Thus, it is particularly important to keep the interest and trust of end-users (Darling 2019, Mosher et al 2020, Sepulveda et al 2020. For that, it is vital for end-users to be able to: recognize both the power and the limitations of existing tools; to know how (e)DNA metabarcoding works and what are the limitations of the technique and, finally, what can the technique offer to environmental managers beyond what current methodologies already do (Darling 2019).…”
Section: Final Considerationsmentioning
confidence: 99%